SOBRE LITERATURA MENOR: A ESCRITA DE DIAMELA ELTIT (Muitas Vozes, 2024)
For a long time, the literary canon dictated the rules within literature, space that was mostly occupied by white men. From Cultural Studies, it has been possible to make room for literatures written by another part of the population, such as women, and so we can now study the writing of Diamela Eltit. The author writes about marginalized minorities from the point of view of someone who lived through the dictatorship of Chile being part of a collective that acted strongly against the dictatorial period, having written and published her first novel at that time. From this, we will talk about the writing of Diamela Eltit and about how it inserts itself into the literary world as a minor literature, from authors such as Deleuze and Guattari (1975) and Lértora (1993), so that it is possible to analyze how Diamela's literature fits into this concept of minor literature and how the markers of her writing coincide with the characteristics of the minor literatures. We understand, finally, that the markers of Diamela's writing characterize her as an author of minor literature, and that writing about these topics covered in this type of literature are fundamental for the formation of the subject.